Rancang Bangun Sistem Informasi Kenaikan Pangkat Pegawai pada Kantor Kecamatan Bukit Intan - marini marini marini (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Promotions were given to the Civil Service for services that has reached the work that has been determined by the government, in practice the process of promotion and making SKKPT in proposing the promotion of Civil Servants particularly at the sub-district government Bukit Intan experienced delays in meeting the needs employee documents on the promotion of civil servants. See the existing problems, the research method used for this research is the method of data collection, system development methodology, system approach method of data collection is done by observation and interviews. System development method used is the method Object Oriented. The method of analysis of existing data will be described in terms of activiy Diagram, Use Case. The depiction of the design of the data base will be described in the form Relation Table, Entity-Relationship Diagram (ERD). Promotion of information system design using Visual Basic 2008 program and to the database using Microsoft Access 2000. With the advancement of Information Systems is a data search process more effective and efficient, so as to support the development of Information Systems at the sub-district promotion Bukit Intan Pangkalpinang.